2017
DOI: 10.1080/10942912.2016.1249797
|View full text |Cite
|
Sign up to set email alerts
|

Aroma formation in Dianhong black tea: Effects of baking

Abstract: Baking is the last, and yet most essential, step in the formation of the final distinct flavour of most black tea products. In this study, the influence of baking on the volatile components of Dianhong black tea, which is one of the most popular black teas in China, was investigated. As a very fast, effective, and simple method for collecting volatiles, headspace solid-phase microextraction (HS-SPME) with a 65 µm PDMS/DVB fibre was used to extract the volatile compounds of Dianhong black tea, and the volatile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The addition of β-glucosidase during black tea processing was found to increase the contents of the volatile monoterpene alcohol compounds, such as linalool and geraniol, in the black teas [38]. The Maillard reactions of tea leaves occurring during the drying process also increased the contents of linalool and its oxides, enhancing the aromas of the black teas [39]. Benzyl alcohol and phenylethyl alcohol were formed by the hydrolysis of benzyl β-D-glucoside with phenylethyl-β-Dglucopyranoside [38,40].…”
Section: 9 X For Peer Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…The addition of β-glucosidase during black tea processing was found to increase the contents of the volatile monoterpene alcohol compounds, such as linalool and geraniol, in the black teas [38]. The Maillard reactions of tea leaves occurring during the drying process also increased the contents of linalool and its oxides, enhancing the aromas of the black teas [39]. Benzyl alcohol and phenylethyl alcohol were formed by the hydrolysis of benzyl β-D-glucoside with phenylethyl-β-Dglucopyranoside [38,40].…”
Section: 9 X For Peer Reviewmentioning
confidence: 96%
“…The addition of βglucosidase during black tea processing was found to increase the contents of the volatile monoterpene alcohol compounds, such as linalool and geraniol, in the black teas [38]. The Maillard reactions of tea leaves occurring during the drying process also increased the contents of linalool and its oxides, enhancing the aromas of the black teas [39]. Benzyl Since the flavour dilution factor is not a direct measure of the odour potency of the aroma compounds in foods, the odour activity values (OAVs), based on accurate quantitative data, are needed to assess the contributions of the flavour compounds [35].…”
Section: 9 X For Peer Reviewmentioning
confidence: 96%
“…This study showed that the tannase enzyme did not significantly affect odor because there were no changes in volatiles compounds. Qiu et al (2017) identified 53 volatile compounds in black tea with the HS-SPME (Head Space -Solid Phase Micro Extraction) extraction method. The most identified volatile compounds from alcohol groups were more than 70%, then aldehydes, hydrocarbons, ketones, and ester.…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…The taste of tea infusion and the sweetness of tea with baking are both improved by the addition of total soluble sugar (Mao et al ., 2018). Alcohols, aldehydes, and ketones, among other aroma compounds, diffuse to the surface of tea to create a pleasant odour that removes off‐flavours and enhances the aroma of tea (Qiu et al ., 2017). Therefore, baking is essential for enhancing the quality, consistency, type of aroma, and flavour of tea products.…”
Section: Introductionmentioning
confidence: 99%